FROM THE HISTORY OF THE LITERARY ENVIRONMENT OF KASHKADARYA OASIS IN THE YEARS OF INDEPENDENCE. (Journal of Universal Science Research, 2023)
This article describes the history of the literary environment of the Kashkadarya oasis and the stages of its development. The literary environment and its trends that emerged after independence are analyzed. A brief analysis of literary and fictional literature on the history of the oasis is also given. It has been considered that during the many thousand years of history of mankind, fiction has always accompanied him, and that this field has developed significantly in the years of independence.